Growth and Financial Appraisal of Intercropping Rattan (Calamus Manan Miq) with Rubber (Hevea Brasiliensis Willd) - Harun, Ismail (1996)
Integrated farming under rubber plantation is a new agroforestry practice in Malaysia. It has lately become more important due to the increasing demand for food and raw materials as a result of increasing population and scarcity of land. Interplanting of rattan under rubber can be one of the systems which can solve the problem of insufficient supply of rattan. The system has been introduced in the 1980 s with the aim of maximising land use as well as to ensure sufficient rattan supply to the industry. Al though the system is now widely accepted by small holders and rubber plantation owners, the re ares till many problems related to the cultivation and management aspects such as the impacts of intercropping and the optimal fertilizer regimes.